Reumidificação, caracterização e secagem de grãos de cevada em leito fixo - Albini, Geisa (Universidade Federal de São Carlos, 2015)
In order to contribute to the improvement of the drying process, the objective of this work was the experimental study on the drying of barley. Barley (Hordeum vulgare) grains of the variety Cauê have been used in this study, as consequence of the scarce information about this material, thus its characterization was necessary, due to the importance of the knowledge of the physical characteristics of the material, such as dimensions, shape, specific mass and porosity, as well as its dependence on different initial moisture contents. The study of the drying kinetics was carried out in a fixed bed dryer with upward air flow in a thin layer. Preliminary experiments were performed to determine the operating conditions of the equipment and to determine the thickness of the thin layer. Drying experiments consisted of obtaining moisture data and temperature versus time, evaluating the influence of the main process operating variables. Based on these data obtained in the drying experiments, carried out at temperatures from 40 to 50°C and air velocity from 0.8 to 4.0 m/s, the influence of the air velocity and temperature drying was evaluated, as well as the procedure of rehumidification of barley grains on the drying kinetics. Kinetic models (Diffusive, Page, Lewis, Herderson and Pabis and Overhults) were fit to drying experimental data. Although the determination coefficient data obtained by the diffusive model are higher than 0,9, experimental data of dimensionless moisture content are underestimated at the intermediate stage to the end of the drying process. The Page model and the Overhults model were appropriate to represent the grains dimensionless moisture content as a function of drying time, but showed an overestimation of the data at the end of the process.
Keywords: Secagem; Leito fixo; Propriedades físicas; Cinética de secagem; Cevada; ENGENHARIAS::ENGENHARIA QUIMICA